Weakly Polarized Organic Cation-Modified Hydrated Vanadium Oxides for High-Energy Efficiency Aqueous Zinc-Ion Batteries - Jia, Xiaoxiao; Liu, Chaofeng; Wang, Zhi; Huang, Di; Cao, Guozhong (Nano-Micro Letters, 2024)
Vanadium oxides, particularly hydrated forms like V2O5·nH2O (VOH), stand out as promising cathode candidates for aqueous zinc ion batteries due to their adjustable layered structure, unique electronic characteristics, and high theoretical capacities. However, challenges such as vanadium dissolution, sluggish Zn2+ diffusion kinetics, and low operating voltage still hinder their direct application. In this study, we present a novel vanadium oxide ([C6H6N(CH3)3]1.08V8O20·0.06H2O, TMPA-VOH), developed by pre-inserting trimethylphenylammonium (TMPA+) cations into VOH. The incorporation of weakly polarized organic cations capitalizes on both ionic pre-intercalation and molecular pre-intercalation effects, resulting in a phase and morphology transition, an expansion of the interlayer distance, extrusion of weakly bonded interlayer water, and a substantial increase in V4+ content. These modifications synergistically reduce the electrostatic interactions between Zn2+ and the V–O lattice, enhancing structural stability and reaction kinetics during cycling. As a result, TMPA-VOH achieves an elevated open circuit voltage and operation voltage, exhibits a large specific capacity (451 mAh g–1 at 0.1 A g–1) coupled with high energy efficiency (89%), the significantly-reduced battery polarization, and outstanding rate capability and cycling stability. The concept introduced in this study holds great promise for the development of high-performance oxide-based energy storage materials. Highlights: 1 A vanadium oxide (TMPA-VOH) is synthesized with trimethylphenylammonium cations chemically pre-inserted into hydrated vanadium oxide. 2 The pre-intercalation of weakly polarized organic cations strategically utilizes both ionic and molecular pre-intercalation effects. 3 TMPA-VOH, with modified crystal structure and morphology, increased V4+ content, and weakened electrostatic interactions between Zn2+ and the V-O lattice, demonstrates enhanced voltage, storage capacity, structural stability, and reaction kinetics.